The use of Deceptive Advertising on Weight Loss Products and its Impact on Generation Z’s Purchase Behavior - Hamann, Kristi (The IIE, 2022)
Deceptive advertising is widespread in the weight loss product market (Cawley et al, 2013). Gradual weight loss is not predominantly appealing to individuals as they usually want faster results; therefore, some people consume products that promise fast weight loss with hardly any physical effort by brands who put misleading information on the product label. (Blanck et al, 2007). Most consumers are unaware of the facts on how to realistically lose weight and are instead drawn into deceptive advertising by companies who advertise false claims (Cawley et al, 2013). Brands are misleading consumers by creating false possibilities of weight loss by using visuals and semiotics on their product advertising. Furthermore, Worldwide obesity has more than doubled since 1980, with 1.9 billion adults being overweight, thus resulting in a plethora of individuals who want to lose weight (World Health Organization, 2020), and brands are taking advantage of this by gaining profit from ineffective, cheap products (Ethan et al, 2016). Research that has been done on Generation Z’s purchase behavior reiterates that the generation wants transparency, authenticity, and honesty from brands. The generation is said to not hesitate to boycott companies over unethical business practices and false advertising (Bapna, 2021). This study will identify whether deceptive advertising in terms of weight loss products will have an impact on Generation Z’s purchase behavior, particularly with regards to how Generation Z are affected by visual and semiotic codes within weight loss product labelling and advertisements. The methodology of this research study took a qualitative approach, where exploratory data was obtained through an online questionnaire, as well as an online focus group. The data findings from both data collection methods provided the researcher with data rich text and audio consisting of opinions, experiences and perceptions which allowed the researcher to obtain in-depth insights. These insights led to a deeper understanding of Generation Z’s purchase behavior with regards to weight loss products, specifically with Generation Z’s opinions and experiences with weight loss product labelling and advertisements. From the research conducted, it was evident that deceptive advertising in the weight loss product market has a moderate effect on Generation Z’s purchase decisions. This is since Generation Z are educated enough around deceptive advertising and how brands use this tool for profit, as they are aware they are being subjected to deceptive advertising; however, they claim they would continue to purchase weight loss products that communicate false claims in hopes that they might lose weight.
Keywords: Buying patterns; Customer behaviour; Diets